Acute intermittent porphyria presenting as recurrent limb weakness - Karki, Binod; Pande, Prakash Raj; Sharma, Arun; Deo, Rajeeb Kumar (Medical Journal of Shree Birendra Hospital, 2013)
Acute intermittent porphyria is a rare autosomal dominant condition of porphyrin metabolism resulting from the half-normal Hydroxy methyl bilane synthase activity. The disorder can present with protean manifestation ranging from acute abdomen, psychosis to gross peripheral neuropathy thus making the diagnosis challenging and misled most of the times. A case of Acute intermittent porphyria with extreme neurological involvement in form of acute onset quadriparesis is presented in this paper. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/44-45 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7910